In-Vitro Antimicrobial Activity And Phytochemical Study Of An Indigenous Plant Species Of Meghalaya - Das, Bhanita; Barman, Kamallochan; Borah, Sudarshana; Kalita, Pallab; Kumari, Sony (Journal of Neonatal Surgery, 2025)
Objective: Antimicrobial activity refers to the ability of substance, such as a drug, chemical, or plant extract to inhibit the growth or destroy microorganisms, including bacteria, fungi, viruses and parasites. The plant Anemone rivularis Buch.-Ham. ex. DC., indigenous to the northeastern state of Meghalaya, is traditionally believed to possess pharmacological properties for the treatment of microbial infections, inflammations, and cancer related conditions. This study aims to evaluate the in-vitro antimicrobial potential and identify the active phytoconstituents present in the leaves of A. rivularis. Methods: The leaves were subjected for methanolic extraction. The crude extracts were tested against Staphylococcus aureus, Streptococcus pyogenes and Escherichia coli for antimicrobial activity using agar well diffusion and UV spectrophotometer methods. Minimum inhibitory concentrations (MICs) for active crude extracts were done using agar well diffusion technique. Results: It was observed that the crude extracts showed highest activity against the selected bacterial strains with minimum inhibitory concentrations (MIC) of 60 µL. The activity indices and zones of inhibition were compared with commercially used standard antibiotic azithromycin and Penicillin G and provide evidence of the methanolic extract's antibacterial efficacy. The UV spectrophotometry method also showed significant inhibition zone at a wavelength of 600nm against the bacterial strains. TLC with phytochemical study showed the presence of active phytoconstituents like flavonoids, tannins, phenolic compounds, triterpenoids & steroids. Conclusion: These results suggest that A. rivularis contains different phytoconstituents having medicinal properties and justify the traditional use for the treatment of antimicrobial diseases. However, research on in-vivo methods along with toxicity study is recommended to validate the safety for society.